Insightful Advancement and Opportunities for Microbial Bioplastic Production - Samadhiya, Kanchan; Sangtani, Rimjhim; Nogueira, Regina; Bala, Kiran (Frontiers in Microbiology, 2022)
Impetuous urbanization and population growth are driving increased demand for plastics to formulate impeccable industrial and biomedical commodities. The everlasting nature and excruciating waste management of petroleum-based plastics have catered to numerous challenges for the environment. However, just implementing various end-of-life management techniques for assimilation and recovery of plastics is not a comprehensive remedy; instead, the extensive reliance on finite resources needs to be reduced for sustainable production and plastic product utilization. Micro-organisms such as bacteria and algae are explored substantially for their bioplastic production repertoire, thus replacing fossil-based plastics sooner or later. Several bacterial strains are reported for their efficacious potential of gathering the bioplastic precursors, whereas the investigation of the microalgal potential for bioplastic synthesis is still in its infancy. Nevertheless, the utilization of pure microbial cultures has led to various operational and economical complications, opening the ventures for the usage of mixed microbial cultures comprising of bacteria and algae for sustainable production of bioplastic. The current review is primarily focused on elaborating the bioplastic production capabilities of different bacterial and algal strains, followed by discussing the quintessence of mixed microbial cultures in the field of bioplastic. The present state-of-the-art of bioplastic, different types of bacterial biopolymers, microalgal biocomposites, operational factors influencing the quality and quantity of bioplastic precursors, embracing the potential of bacteria-algae consortia as well as the current global status-quo of bioplastic production has been summarized extensively.